Customized Integrating-Sphere System for Absolute Color Measurement of Silk Cocoon with Corrugated Microstructure - Riaz Muhammad; Seok-Ho Lee; Kay-Thwe Htun; Ezekiel Edward Nettey-Oppong; Ahmed Ali; Hyun-Woo Jeong; Young-Seek Seok; Seong-Wan Kim; Seung-Ho Choi (Sensors, 2023)
Silk fiber, recognized as a versatile bioresource, holds wide-ranging significance in agriculture and the textile industry. During the breeding of silkworms to yield new varieties, optical sensing techniques have been employed to distinguish the colors of silk cocoons, aiming to assess their improved suitability across diverse industries. Despite visual comparison retaining its primary role in differentiating colors among a range of silk fibers, the presence of uneven surface texture leads to color distortion and inconsistent color perception at varying viewing angles. As a result, these distorted and inconsistent visual assessments contribute to unnecessary fiber wastage within the textile industry. To solve these issues, we have devised an optical system employing an integrating sphere to deliver consistent and uniform illumination from all orientations. Utilizing a ColorChecker, we calibrated the RGB values of silk cocoon images taken within the integrating sphere setup. This process accurately extracts the authentic RGB values of the silk cocoons. Our study not only helps in unraveling the intricate color of silk cocoons but also presents a unique approach applicable to various specimens with uneven surface textures.